Effect Of Sesame Seed Paste On The Quality Of Mini Chevon Patties - Jeyapriya, S; Pal , U K; Rajkumar, V; Mandal , P K; Kasthuri , S (Journal of Meat Science, 2023)
A study was undertaken to find the effect of sesame seed paste (SSP) as fat replacer in mini chevon patties. Standardized recipe of chevon patties containing goat meat (70%) and chevon fat (7%) was considered as control. Sesame seed paste (SSP)was incorporated at 1.4%, 2.8%, and 4.2% levels in the formulation by replacing chevon fat at 20, 40 and 60% levels, respectively. Three batches each of control and sesame seed paste added chevon patties were prepared in the experiment and were subjected to physicochemical, proximate and sensory analysis. No significant (P>0.05) difference was noticed in pH of patties and batter in control and treatments. The control patties had significantly (P<0.05) higher emulsion stability(%), moisture(%), and fat (%) than the other treatments. The patties prepared with 2.8% and 4.2% SSP showed significantly higher cooking yield(%), protein and ash contents than control and treatments. The patties prepared with 2.8% SSP had significantly (P<0.05) higher sensory scores compared to patties containing 4.2% SSP. The level of 2.8% SSP also showed significantly (P<0.05) higher fiber content, better fatty acid and amino acid profile than the control. Thus sesame seed paste appeared to be a better fat replacer without affecting quality of chevon patties.